Synchronization of Neural Networks with Mixed Time Delays under Information Constraints - Dedong Yang; He-Xu Sun; Peng Yang; Tai-Hang Du (Abstract and Applied Analysis)
This paper investigates the synchronization problem of neural networks with mixed time delays under information constrains. The designed synchronization scheme is built on the framework of hybrid systems. Besides including nonuniform sampling, some other characteristics, such as quantization, transmission-induced delays, and data packet dropouts, are also considered. The sufficient condition that depended on network characteristics is obtained to guarantee the remote asymptotical synchronization of neural networks with mixed time delays. A numerical example is given to illustrate the validity of the proposed method.